Strategi Pengembangan Brand Identity dalam Industri Fashion Brand HIRKA Shoes - Islami, Putri Bela; Rizal, Edwin; Mulyana, Slamet (STKIP PGRI SITUBONDO, 2024)
In the fashion industry, forming a brand identity serves various crucial functions. This research focuses on brand identity development strategies in the fashion industry with a case study on the HIRKA brand. The research method employed is qualitative literature review. The findings indicate that the majority of respondents are unfamiliar with the HIRKA brand, indicating significant opportunities for brand development and increased brand awareness. In the analysis of brand identity, four dimensions are found to be important: product, organizational, personality, and symbolic. Despite implementing several innovations in products and marketing approaches, HIRKA still faces challenges in brand recognition. Based on brand development strategies by Tjiptono, this research suggests HIRKA pursue product development, refinement, modification, or new brand development through research and development to enhance consumer awareness and preference. In conclusion, branding success can be achieved through continuous innovation, hard work, and perseverance, as demonstrated by the HIRKA case study. These findings provide valuable insights for companies in the fashion industry striving to build and strengthen their brand identities. Keywords: brand development, brand identity, fashion, products